Combining Realism with Rigour: An Evaluation of a National Kitchen Garden Program in Australian Primary Schools. (December 2014) - Yeatman, Heather; Quinsey, Karen; Dawber, James; Nielsen, Wendy; Condon-Paoloni, Deanne; Eckermann, Simon; Morris, Darcy; Grootemaat, Pam; Fildes, David
School garden and kitchen-based activities have potential as health-promoting school initiatives but lack well-designed evaluation frameworks. This article outlines an evaluation of a national kitchen garden program conducted in Australian primary schools. The aim was to evaluate the implementation and impact of a national garden and kitchen program in Australia, including child and health-related impacts of the program, and program implementation factors. The evaluation was undertaken using a multi-component, hierarchical evaluation framework that incorporated a modified case-control design and mixed methods. A cross-section of initiative (N=28) and comparison (N=14) schools was included. The Stephanie Alexander Kitchen Garden model achieved overall improvements in students' food choices (as reported by students; t=2.26, p=0.024) and kitchen lifestyle behaviours (as reported by parents; t=2.35, p=0.019); female students and students from provincial schools had statistically greater improvements in food choices than other students and girls showed higher scores than boys (t=6.19, p<0.001). The evaluation framework generated data that addressed the evaluation questions. Program integrity was maintained. Factors related to the program's implementation, sustainability, generalisability and return on investment were reported. Factors impacting the evaluation included lack of baseline data, specific data collection methods and time issues. The main conclusion drawn from the study is that structured hierarchical, multi-component evaluation is needed to provide practical insights into effective health promotion initiatives in schools.